Respon Nahdlatul Ulama terhadap Gempuran Aliran Fundamental; Telaah Kritis Radikalisme Intoleran dan Pudarnya Moderatisme Islam - Bakri, Maskuri (Universitas Islam Tribakti (UIT) Lirboyo Kediri, 2021)
Islam that is displayed by mainstream groups is now getting great onslaguht from non-mainstream from transnational circles with diverse faces, this second group is more violent and has a more structured and massive regeneration system and tends to dominate strategic institutions in Indonesia, with a fiercer appearance. and openly, even carrying the caliphate system in government, and trying to enter the national political arena as a strategic vehicle. On the other hand, the mainstream group began to feel and received strong pressure from the non-mainstream so that it began to step aside, even though it had long colored the nation and state of Indonesia, the other side of the non-mainstream group began to take center stage. However, it turns out that there is still hope that educated mainstream groups will begin to show their potential even though they have not been properly consolidated in facing non-mainstream groups. Islam that is displayed by mainstream groups has actually got a place from many circles in this world, because their life always adheres to the principles of tasamuh, tawassud, tawazzun, al'adl, and amar ma'ruf nahi munkar consistently, even in the global era it can also adapt to the life of time.